(untitled) (Baghdad Science Journal, 2005)
In this study serum total sailie acid concentration were tested as a scrological marker of discases activity to cvalute the result of the test in the diagonosis oe enteric fever(TSA) was measured in the serum od (50) patines with typhi fever(50)pa-tients